The Kibar Method BTHQ Learning Curriculum on Improving the Cognitive Aspects of Muhammadiyah Elementary School Students Karangkajen - Ariq Nurjannah Irbah; Prasetiyo, Eko; Putro, Khamim Zarkasi (HEUTAGOGIA: Journal of Islamic Education, 2022)
This study was to determine the improvement of students' cognitive aspects with the Kibar method of BTHQ learning at SD Muhammadiyah Karangkajen. The design of this research is qualitative, with a qualitative descriptive approach. The subjects of this study were grade 1 students of SD Muhammadiyah Karangkajen. The results showed that BTHQ activities: 1) provide knowledge, 2) understanding and good reading methods using makharijul letters, 3) providing advice or motivation so that children take BTHQ on time, 4) providing educational punishments for students, 5) conduct an evaluation after the BTHQ activity. This case study focuses on the BTHQ learning curriculum carried out by tutors/teachers through the kibar method for students at SD Muhamadiyah Karangkajen. This case study shows that, with the BTHQ learning curriculum by competent tutors/teachers, it can improve the cognitive aspects of children/students, as a basis for understanding PAI family learning. This study contributes to the ease of learning with the children's BTHQ curriculum through the waving method. In addition, this study recommends that teachers apply this method to improve the cognitive aspects of BTHQ through supportive learning innovations.